Physico-chemical, thermal, and morphological characterization of biomass-based novel microcrystalline cellulose from Opuntia ficus-indica shoot: a biomass to biofiller approach - Palaniappan, Murugesan (Biomass conversion and biorefinery, 2025)
Cellulose, an abundant biopolymer, is present in an extensive variety of materials derived from plants. At this time, waste management is the predominant subject of scientific investigation. Presently, the utilisation of phytochemical-rich plants is widespread. The microcrystalline cellulose extraction procedure of Opuntia ficus-indica involves a predominant process such as alkali treatment, surface reaction, acid hydrolysis, bleaching, and neutralization. The extracted cellulose was then finalized and characterized using the Fourier transform spectroscopy for structural analysis. The density of the extracted cellulose is found to be 1.395 g/cm 3 , and the yield % is noted as 70.98%. X-ray diffraction spectroscopy was employed to determine the crystallinity of the sample; the crystalline size and crystallinity index were determined to be 6.92 nm and 50.09%, respectively. The thermal study shows that the microcrystalline cellulose can withstand temperature up to 303.08 °C found using differential thermogram curve analysis. The surface parameters are well explained, and the microcrystalline cellulose had allowable surface parameters. The scanning electron images shows that the microcrystalline cellulose contain smooth, rod-shaped surface. The elemental analysis shows organic nature of cellulose which comprise of higher amount of carbon and oxygen. The results of the particle size study indicate that the majority of the particles are larger than 150 μm. The properties of cellulose are more applicable for polymer reinforcement applications.